Hospital readmissions of patients with heart failure from real world: timing and associated risk factors - Wideqvist, Maria; Cui, Xiaotong; Magnusson, Charlotte; Schaufelberger, Maria; Fu, Michael (ESC Heart Failure, 2021)
Aims This study aims to investigate hospital readmissions and timing, as well as risk factors in a real world heart failure (HF) population. Methods and results All patients discharged alive in 2016 from Sahlgrenska University Hospital/Östra, Gothenburg, Sweden, with a primary diagnosis of HF were consecutively included. Patient characteristics, type of HF, treatment, and follow‐up were registered. Time to first all‐cause or HF readmission, as well as number of 1 year readmissions from discharge were recorded. In total, 448 patients were included: 273 patients (mean age 78 ± 11.8 years) were readmitted for any cause within 1 year (readmission rate of 60.9%), and 175 patients (mean age 76.6 ± 13.7) were never readmitted. Among readmissions, 60.1% occurred during the first quarter after index hospitalization, giving a 3 month all‐cause readmission rate of 36.6%. HF‐related 1 year readmission rate was 38.4%. Patients who were readmitted had significantly more renal dysfunction (52.4% vs. 36.6%, P = 0.001), pulmonary disease (25.6% vs. 15.4%, P = 0.010), and psychiatric illness (24.9% vs. 12.0%, P = 0.001). Number of co‐morbidities and readmissions were significantly associated (P < 0.001 for all cause readmission rate and P = 0.012 for 1 year HF readmission rate). Worsening HF constituted 63% of all‐cause readmissions. Psychiatric disease was an independent risk factor for 1 month and 1 year all‐cause readmissions. Poor compliance to medication was an independent risk factor for 1 month and 1 year HF readmission. Conclusions In our real world cohort of HF patients, frequent hospital readmissions occurred in the early post‐discharge period and were mainly driven by worsening HF. Co‐morbidity was one of the most important factors for readmission.